TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION METHOD IN PATIENTS WITH XEROSTOMIA (ETIMA, 2024)
Patients with salivary gland hypofunction typically complain of dry mouth, difficulty chewing, swallowing and/or speaking; they hardly tolerate spicy, acidic, and crunchy food and often times report taste changes or difficulty wearing dentures. It can also increase the chance of developing dental decay, demineralization of teeth, tooth sensitivity, and oral infections. The goals of treating xerostomia include identifying the possible causes, relieving discomfort, and preventing complications. In this study, we investigate the most effective frequency to increase salivary secretion, without side effects on the skin and orofacial structures. Transcutaneous electric nerve stimulation (TENS) is a simple, inexpensive, and non-invasive modality that uses electric current to activate nerves for therapeutic reasons. It is a non-pharmacological method of pain management for which it is widely used. Application of electric impulses to one or more of the three components of the salivary reflex arch should theoretically improve salivary secretion and lessen the various long-term effects of hyposalivation. For this study were analyzed totally 23 published studies in the last 10 years. The study is made on narrative review of published articles that were go into the related subject, evaluation of the impact of a transcutaneous electrical nerve stimulation (TENS) system on patients' dry mouth and salivary flow rates. The TENS unit was effective in increasing the quantity of stimulated saliva and was also found to be more effective in increasing saliva in diabetic individuals. From the results of the study, it can be concluded that TENS was effective in increasing the salivary flow rate in hyposalivatory patients with residual saliva.
Keywords: Salivary glands; xerostomia; saliva flow rate; dry mouth therapy; TENS; hyposalivation treatment